Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan Adobe Flash CS 6 Pada Materi Trigonometri - Indah Pujiarti; Rosita Dwi Ferdiani; Trija Fayeldi (JRPM (Jurnal Review Pembelajaran Matematika), 2022)
In the era of industrial revolution 4.0 and community technology 5.0, smartphones are currently very widely used by educational practitioners as a medium for learning mathematics. It aims to attract students' interest in learning mathematics that is considered difficult by students such as trigonometry material. A lot of software is used to make android-based learning media for smartphones, one of which is Adobe Flash CS 6. This research is ADDIE version development research which includes five levels, specifically: Analysis, Design, Development, Implementation, and Evaluation. The instruments used are professional validation questionnaires and scholar response questionnaires. The validation expert concludes that Android-based mathematics learning media using Adobe Flash CS 6 on trigonometry material is included in the category "very feasible and can be used with a little revision." While the results of the student response questionnaire obtained a very good percentage of student responses and got the "very practical" category.